Ultrastructural study of the cuticle and epidermis in Pseudochordodes bedriagae - Villalobos, Leonor Cristina de (2001)
The light-microscopic and ultrastructural characteristics of Nematomorpha (Gordiacea) integument are described. Nine male Pseudochordodes bedriagae specimens were collected in the 1997 spring-summer period from the Sauce Chico stream in the Sierra de la Ventana, province of Buenos Aires, Argentina. Of these samples, two were analyzed using scanning electron microscopy (SEM) and the other two using transmission electron microscopy (TEM) in order to establish their morphological characteristics. The morphology of the three integumentary components (epidermis, cuticle and epicuticle) is described. Comparing our findings with those of previous studies, numerous similarities are pointed out. Some variants found would probably be related more to the various criteria of interpreting cut incidences and/or fractures than to actual differences. We assume that the different zones of the cuticle and epicuticle are segregated at the germinal stratum level by the epidermal cells, which would later undergo a slow process of maturation until their exocytosis at the level of the free epicuticular surface.